2021
DOI: 10.25518/0037-9565.10457
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between biophysical indices and Land Surface Temperature using remote sensing and GIS in Guelma city (Algeria)

Abstract: Urbanization is a phenomenon that is driven by humans. It has significantly influenced biodiversity, ecosystem processes and regional climate. This work explores the relationship between seven biophysical variables (NDVI, SAVI, Greenness, Albedo, DBI, NDBI, and NDBaI indices), and LST over a period of 30 years (1990–2020), based on remote sensing & GIS. A time-series of Landsat images TM, ETM+ and OLI/TIRS data as well as various geospatial approaches were used to facilitate the analysis. The findings have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…2021), who revealed a negative correlation between LST and NDVI. Furthermore, the negative correlation between LST and SAVI in the dry season was consistent with the findings of Guechi et al (2021). In addition, the negative correlation between LST and NDVI and EVI agrees with the findings by Alademomi et al (2020).…”
Section: Relationship Between Lst and The Vis In Dry And Rainy Seasonssupporting
confidence: 89%
See 1 more Smart Citation
“…2021), who revealed a negative correlation between LST and NDVI. Furthermore, the negative correlation between LST and SAVI in the dry season was consistent with the findings of Guechi et al (2021). In addition, the negative correlation between LST and NDVI and EVI agrees with the findings by Alademomi et al (2020).…”
Section: Relationship Between Lst and The Vis In Dry And Rainy Seasonssupporting
confidence: 89%
“…Previous studies on the correlation between LST and NDVI were primarily concerned with examining the influence of urbanization on anomalous heat (Urban Heat Island) in cities. Some of these studies can be found in Deng et al (2018), Guechi et al (2021), and Koko et al (2021). Furthermore, Macarof et al (2018) investigated the correlation between LST and NDVI, MSAVI, and EVI only in the warmth season.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the magnitude in which urban factors impact urban climate remains elusive and this type of study contributes to this gap in the field of knowledge [40,41]. To determine the extent to which biophysical characteristics could describe the distribution of LST, we proposed three different methods, aiming for a comprehensive study and comparative analysis.…”
Section: Methods To Identify Relationships Of Biophysical Variabless ...mentioning
confidence: 99%
“…This practice is spread in the major part of agricultural land including cereal crops. The objective of this study is to identified the cereal areas in the department of Sidi bel Abbes during the growing season 2020-2021 using sentinel2A time series images (Guechi et al, 2021), then to catch the relationship of crop duration from different plots at local scale according to growing season of NDVI values (field observations, May 2021) (Maselli & Rembold, 2001;Chehat, 2007).…”
Section: Introductionmentioning
confidence: 99%